Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/chem.202301270
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and Predominantly Localized Boron Radical from the Reduction of a Three‐Dimensional Analogue of NHC‐Stabilized Borafluorenium

Abstract: In this contribution, we reported the three-dimensional (3D) analogues of N-heterocyclic carbene (NHC)stabilized 9-borafluorenium and 9-borafluorene radical. The radical was fully characterized by cyclic voltammetry (CV), UV-Vis absorption spectroscopy, electron paramagnetic reso-nance (EPR) and single-crystal X-ray diffraction analyses. The distinct boron-centered radical character of 9-borafluorene radical was corroborated by DFT calculations and EPR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 101 publications
0
1
0
Order By: Relevance
“…4 b Moreover, the chloro derivative reacts with N-heterocyclic carbenes (NHCs), resulting in the formation of either an NHC adduct (Fig. 1b, middle), 8 or an NHC-stabilized 3D 9-borafluorenium cation. 8 Additionally, the first 3D 9-borafluorene radical could be attained upon single-electron reduction of the 3D 9-borafluorenium cation (Fig.…”
mentioning
confidence: 99%
“…4 b Moreover, the chloro derivative reacts with N-heterocyclic carbenes (NHCs), resulting in the formation of either an NHC adduct (Fig. 1b, middle), 8 or an NHC-stabilized 3D 9-borafluorenium cation. 8 Additionally, the first 3D 9-borafluorene radical could be attained upon single-electron reduction of the 3D 9-borafluorenium cation (Fig.…”
mentioning
confidence: 99%
“…9 Additionally, owing to the unique hyperconjugation between carborane cluster and outer-cage groups, 10–12 the 3D carborane cages hold substantial promise in replacing conventional 2D aromatic aryl groups for the construction of optoelectronic materials. 3,13–16 However, despite these intriguing aspects, research on carboranyl boranes is still relatively lagging compared to traditional organoboranes.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow electron delocalization through the cluster and make it potentially useful for constructing conjugated materials. However, both experimental and theoretical studies show weak communication between 2D π-systems and 3D carborane cages. Hawthorne, Low, and co-workers reported complexes 1 – 3 (Scheme ) with two metal centers separated by p -carborane and concluded that the coupling between the metal centers is weak. Further studies on the photophysics of dicarbazole-substituted m - and p -carboranes indicate that m - and p -carboranes are insulators that completely separate the two carbazole electronic systems. , …”
Section: Introductionmentioning
confidence: 99%